2006
DOI: 10.1007/s00120-006-1015-9
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitsbezogene Lebensqualität bei Kindern mit Spina bifida

Abstract: Despite the fact that children with MMC often suffer from severe physical limitations, their HRQoL is not necessarily lower than that of healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, having a serious illness does not necessarily mean a lower quality of life. A study of healthrelated quality of life in children and adolescents with spina bifida showed that there was no difference in health-related quality of life between patients and healthy children and adolescents [16]. Also, in the quality-of-life surveys of patients with esophageal atresia [11,12], asthma and type 1 diabetes [5,17], heart defects [18], cancer [19], or hereditary diseases such as Marfan syndrome [20], it was found that the diseases do not necessarily result in a poorer quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, having a serious illness does not necessarily mean a lower quality of life. A study of healthrelated quality of life in children and adolescents with spina bifida showed that there was no difference in health-related quality of life between patients and healthy children and adolescents [16]. Also, in the quality-of-life surveys of patients with esophageal atresia [11,12], asthma and type 1 diabetes [5,17], heart defects [18], cancer [19], or hereditary diseases such as Marfan syndrome [20], it was found that the diseases do not necessarily result in a poorer quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Children 2024, 11, 536 2 of 16 scale" have been developed [2]. Abdominal pain, loose stools, poor eating habits, and fatigue affect the quality of life for adults.…”
Section: Introductionmentioning
confidence: 99%